1996
DOI: 10.1200/jco.1996.14.10.2803
|View full text |Cite
|
Sign up to set email alerts
|

Intensive oral methotrexate protects against lymphoid marrow relapse in childhood B-precursor acute lymphoblastic leukemia.

Abstract: PURPOSE To describe the use of combination chemotherapy, including divided-dose oral methotrexate (dMTX), for children with B-precursor acute lymphoblastic leukemia (ALL). dMTX produced prolonged MTX exposure on an outpatient basis. PATIENTS AND METHODS Two hundred forty-three patients were treated from January 1986 to May 1992. dMTX was given weekly during consolidation and biweekly for the first 16 months of continuation therapy with mercaptopurine (6-MP) and asparaginase (L-ASP). Initially, etoposide (VP-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Mucosal toxicity was dose limiting at higher doses and ameliorated by dose reduction and/or the addition of leucovorin rescue. The observed toxicity at the maximum tolerated dose was similar to that observed in patients given methotrexate (25 mg/m 2 ) q6H for four doses weekly as a component of therapy for ALL (18).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Mucosal toxicity was dose limiting at higher doses and ameliorated by dose reduction and/or the addition of leucovorin rescue. The observed toxicity at the maximum tolerated dose was similar to that observed in patients given methotrexate (25 mg/m 2 ) q6H for four doses weekly as a component of therapy for ALL (18).…”
supporting
confidence: 51%
“…Because the most accepted role for an antifolate is not as a single agent, but in the setting of multiagent, post-remission therapy, our goal in the clinical development of aminopterin has been predicated on finding a dose and schedule to mimic the divided-dose oral methotrexate that has been used in post-induction therapy for patients with ALL (18,19). The maximum tolerated dose of aminopterin on our phase I trial was 2 mg/m 2 /dose q12 hours for two doses weekly (15).…”
mentioning
confidence: 99%
“…Using a different rescue regimen, repeated oral methotrexate has been used successfully for consolidation by the DallasFort Worth group. 18 A recently completed POG ALL study for standard risk is evaluating divided dose oral methotrexate for delayed intensification prior to maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Potential reasons for these neurotoxicities have been reviewed in a previous publication, 34 Overall outcome data from this clinical trial compare favorably with previous POG trials and those of other groups treating children for HR-ALL (62-75%). [9][10][11][12][13][14][15][16][17][18][19][20] Because risk group criteria differ among large cooperative groups treating childhood ALL, external comparisons are difficult and hazardous. However, 66% of the patients in this study would be considered high risk by the CTEP/NCI consensus risk group definition (age у10 years, or WBC у50 000) thus adding some validity to cross comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Increased toxicity was also noted with the aggressive use of myelosuppressive agents. 9,13,14,16,18,[19][20][21][22] However, preliminary results from POG 8698 suggested that early intensification with the less toxic combination of intermediate-dose methotrexate (MTX) and mercaptopurine (MP) might be as effective as the more myelosuppressive combinations used in another POG pilot study (POG 8398) for HR-ALL. 13,17 In 1991, the POG opened a group-wide randomized phase III clinical trial (POG 9006) to treat children with HR-ALL.…”
Section: Introductionmentioning
confidence: 99%